2022
DOI: 10.5194/tc-16-4727-2022
|View full text |Cite
|
Sign up to set email alerts
|

Broadband spectral induced polarization for the detection of Permafrost and an approach to ice content estimation – a case study from Yakutia, Russia

Abstract: Abstract. The reliable detection of subsurface ice using non-destructive geophysical methods is an important objective in permafrost research. The ice content of the frozen ground is an essential parameter for further interpretation, for example in terms of risk analysis and for the description of permafrost carbon feedback by thawing processes. The high-frequency induced polarization method (HFIP) enables the measurement of the frequency-dependent electrical conductivity and permittivity of the subsurface, in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Auty and Cole, 1952;Bittelli et al, 2004;Grimm et al, 2010;Limbrock and Kemna, 2022) and at the field-scale (e.g. Grimm and Stillman, 2015;Mudler et al, 2022) revealing the temperature-dependent relaxation behaviour of ice (Auty and Cole, 1552) at higher frequencies (with the ice relaxation peak frequency observed in the range between 1 and 45 kHz). By fitting a two-component Cole-Cole model to the SIP data, either for single laboratory measurements (Limbrock and Kemna, 2022) or within a 2-D inversion for field data, Mudler et al (2022) separated the different polarization responses and estimated subsurface ice content using an existing two-component complex resistivity model of frozen soil considering the ice relaxation as the dominant process.…”
Section: Temporal Variability Of the Phase Frequency Effect And Unfro...mentioning
confidence: 99%
See 2 more Smart Citations
“…Auty and Cole, 1952;Bittelli et al, 2004;Grimm et al, 2010;Limbrock and Kemna, 2022) and at the field-scale (e.g. Grimm and Stillman, 2015;Mudler et al, 2022) revealing the temperature-dependent relaxation behaviour of ice (Auty and Cole, 1552) at higher frequencies (with the ice relaxation peak frequency observed in the range between 1 and 45 kHz). By fitting a two-component Cole-Cole model to the SIP data, either for single laboratory measurements (Limbrock and Kemna, 2022) or within a 2-D inversion for field data, Mudler et al (2022) separated the different polarization responses and estimated subsurface ice content using an existing two-component complex resistivity model of frozen soil considering the ice relaxation as the dominant process.…”
Section: Temporal Variability Of the Phase Frequency Effect And Unfro...mentioning
confidence: 99%
“…Grimm and Stillman, 2015;Mudler et al, 2022) revealing the temperature-dependent relaxation behaviour of ice (Auty and Cole, 1552) at higher frequencies (with the ice relaxation peak frequency observed in the range between 1 and 45 kHz). By fitting a two-component Cole-Cole model to the SIP data, either for single laboratory measurements (Limbrock and Kemna, 2022) or within a 2-D inversion for field data, Mudler et al (2022) separated the different polarization responses and estimated subsurface ice content using an existing two-component complex resistivity model of frozen soil considering the ice relaxation as the dominant process. However, such broadband spectral induced polarization measurement device (i.e., the Chameleon-2 used in the study of Mudler et al, 2022) is still not suited for monitoring and cannot be used to perform an extensive mapping as presented here.…”
Section: Temporal Variability Of the Phase Frequency Effect And Unfro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the applicability of sEIT at the field scale (e.g. Kemna, 2000;Flores Orozco et al, 2012a;Günther and Martin, 2016;Maurya et al, 2018;Mudler et al, 2022). Yet, most of these studies only analysed frequencies well below 1 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…Maierhofer et al (2022) directly measured the polarization effect at a frequency of 75 Hz to improve the discrimination between frozen and unfrozen ground in an ice-bearing talus slope in Switzerland. Mudler et al (2022) investigated the application of IP measurements at high frequencies (kHz range) to quantify ice content directly based on the relaxation frequency of ice (Zorin and Ageev, 2017). However, to the best of our knowledge, no study examined the potential of IP data for the estimation of water content and hydraulic conductivity in a rock glacier or other alpine permafrost landforms yet.…”
mentioning
confidence: 99%